Sex Differences and Regulatory Actions of Estrogen in Cardiovascular System - Ueda, Kazutaka; Fukuma, Nobuaki; Adachi, Yusuke; Numata, Genri; Tokiwa, Hiroyuki; Toyoda, Masayuki; Otani, Akira; Hashimoto, Masaki; Liu, Pang-Yen; Takimoto, Eiki (Frontiers in Physiology, 2021)
Great progress has been made in the understanding of the pathophysiology of cardiovascular diseases (CVDs), and this has improved the prevention and prognosis of CVDs. However, while sex differences in CVDs have been well documented and studied for decades, their full extent remains unclear. Results of the latest clinical studies provide strong evidence of sex differences in the efficacy of drug treatment for heart failure, thereby possibly providing new mechanistic insights into sex differences in CVDs. In this review, we discuss the significance of sex differences, as rediscovered by recent studies, in the pathogenesis of CVDs. First, we provide an overview of the results of clinical trials to date regarding sex differences and hormone replacement therapy. Then, we discuss the role of sex differences in the maintenance and disruption of cardiovascular tissue homeostasis.